Jobs and the labor force of tomorrow : migration, training, and education (University of Illinois Press, 2017)
The new volume in the Urban Agenda series addresses the challenges shaping the development of human capital in metropolitan regions. The articles, products of the 2016 Urban Forum at the University of Illinois at Chicago, engage with the overarching idea that a dynamic metropolitan economy needs a diverse, trained, and available workforce that can adapt to the needs of commerce, industry, government, and the service sector. Authors explore provocative issues like the jobless recovery, migration and immigration, K12 education preparedness, the urban-oriented gig economy, postsecondary workforce training, and the recruitment and professional development of millennials. Provided by publisher.
Keywords: Labor market.; Labor supply.; Employment (Economic theory); Marché du travail.; Emploi.; employing.; EDUCATION / Urban; Labor market; Labor supply